A study of lipolysis induced by adjuncts from edible Aspergillus sp. solid culture products on ripened semi‐hard cheese. (4th February 2022) - Chintagavongse, Napaporn; Takiguchi, Hayate; Ming‐Hsuan, Chi; Tamano, Koichi; Hayakawa, Toru; Wakamatsu, Jun‐ichi; Mitani, Tomohiro; Kumura, Haruto
Abstract: BACKGROUND: Aspergillus sp. has been used in traditional Japanese fermented foods. Protease‐containing culture products of A. oryzae have been applied as the adjunct enzyme source to enrich the flavor in ripened cheese. Although proteolysis was stimulated, the increase of free fatty acids (FFA) was recognized in some products. Since an excess amount of FFA accumulation can cause rancidity in cheese products, the assessment of lipase activity was considered to be essential for the cheese adjunct preparation. RESULTS: Although an equal lipase activity from the adjunct materials of A. kawachii NBRC 4308, A. luchuensis RIB 2604 and A. oryzae AHU 7139 was applied to semi‐hard cheese, the FFA level was significantly higher in A. oryzae cheese than in the others. Furthermore, the profiles of volatile components were different in experimental cheeses. An in vitro study with experimental curds demonstrated that the high FFA might not depend on the lipase retainability on curds. On the contrary, the pronounced activation of the lipases occurred in A. oryzae after incubation with the curds. Moreover, incubation of the insoluble lipase that had been attached to the cells with skim milk curd extracts allowed the release of lipases from the cells into the medium with remarkable activation. CONCLUSION: A. oryzae AHU 7139 possessed a complex lipolytic system comprising extracellular and cell‐binding lipases that were attributed to the increase in FFA in A. oryzae cheese. © 2022 Society of Chemical Industry.